Association of Collateral Status and Ischemic Core Growth in Patients With Acute Ischemic Stroke. (12th January 2021) - Lin, Longting; Yang, Jianhong; Chen, Chushuang; Tian, Huiqiao; Bivard, Andrew; Spratt, Neil J.; Levi, Christopher R.; Parsons, Mark W.
Abstract : Objective: To test the hypothesis that patients with acute ischemic stroke with poorer collaterals would have faster ischemic core growth, we included 2 cohorts in the study: cohort 1 of 342 patients for derivation and cohort 2 of 414 patients for validation. Methods: Patients with acute ischemic stroke with large vessel occlusion were included. Core growth rate was calculated by the following equation: core growth rate = acute core volume on CT perfusion (CTP)/time from stroke onset to CTP. Collateral status was assessed by the ratio of severe hypoperfusion volume within the hypoperfusion region of CTP. The CTP collateral index was categorized in tertiles; for each tertile, core growth rate was summarized as median and interquartile range. Simple linear regressions were then performed to measure the predictive power of CTP collateral index in core growth rate. Results: For patients allocated to good collateral on CTP (tertile 1 of collateral index), moderate collateral (tertile 2), and poor collateral (tertile 3), the median core growth rate was 2.93 mL/h (1.10–7.94), 8.65 mL/h (4.53–18.13), and 25.41 mL/h (12.83–45.07), respectively. Increments in the collateral index by 1% resulted in an increase of core growth by 0.57 mL/h (coefficient 0.57, 95% confidence interval [0.46, 0.68], p < 0.001). The relationship of core growth and CTP collateral index was validated in cohort 2. An increment in collateral index by 1% resulted in an increase of core growth by 0.59 mL/h (coefficient 0.59 [0.48–0.71], p < 0.001) in cohort 2. Conclusion: Collateral status is a major determinant of ischemic core growth.